2010
DOI: 10.1021/jp104894a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Single-Walled Carbon Nanotubes with Poly(methyl methacrylate) by Emulsion Polymerization

Abstract: Covalent grafting of acrylate-functionalized single-walled carbon nanotubes (SWCNTs) with poly(methyl methacrylate) was accomplished by emulsion polymerization using sodium dodecylbenzene sulfonate (SDBS) as an emulsifying agent. The acrylate-functionalized SWCNTs with polymerizable vinyl groups on their surfaces were prepared by a reaction sequence involving oxidation, hydroxylation, and vinylation reactions. The as-prepared acrylate-functionalized SWCNTs were then dispersed in water in the presence of SDBS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…20 Then, depending on the kind of interactions between the grafted functional molecular architectures, the formation of either porous or compact films can be observed. Recent examples of hybrid inorganic-organic nanostructures include the functionalization of surface-confined ester polymer chains with dibenzocyclooctynes; 21 the construction of molecular multilayer assemblies by click chemistry; 22,23 the binding of PMMA on metal surfaces by surface-initiated atom transfer radical polymerization (ATRP); [24][25][26] the combined Langmuir-Blodgett and ATRP techniques on silicon; 27 the growth of homopolymers and block copolymers on silicon; 28 the growth of thin conductive polymer films of regioregular head-to-tail poly(3-alkylthiophenes) via a surface-initiated polycondensation reaction; 29 the synthesis of engineered anisotropic nanofilms and the pattering of silylated substrates; 30,31 the grafting of polymers on carbon nanotubes, [32][33][34][35][36][37] on carbon nanofibers 38 and on graphene oxide; 39 the ATRP of covalently linked polymer chains on the lamellae of a zirconium phosphonate; 40 the ATRP of PMMA on ZnO nanowires; 41 the grafting of PMMA onto silica nanoparticles; 42 the patterning of covalent organic monolayers on Si etc. 43 Moreover, interesting uses of diazonium salts as coupling agents have been recently provided in a reaction in which some azide-funtionalized, hydrolyzed poly(glycidyl methacrylate) was clicked to alkynylated carbon nanotubes, prepared using in situ-generated diazonium salts, and used as initiators for surface-confined photopolymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…20 Then, depending on the kind of interactions between the grafted functional molecular architectures, the formation of either porous or compact films can be observed. Recent examples of hybrid inorganic-organic nanostructures include the functionalization of surface-confined ester polymer chains with dibenzocyclooctynes; 21 the construction of molecular multilayer assemblies by click chemistry; 22,23 the binding of PMMA on metal surfaces by surface-initiated atom transfer radical polymerization (ATRP); [24][25][26] the combined Langmuir-Blodgett and ATRP techniques on silicon; 27 the growth of homopolymers and block copolymers on silicon; 28 the growth of thin conductive polymer films of regioregular head-to-tail poly(3-alkylthiophenes) via a surface-initiated polycondensation reaction; 29 the synthesis of engineered anisotropic nanofilms and the pattering of silylated substrates; 30,31 the grafting of polymers on carbon nanotubes, [32][33][34][35][36][37] on carbon nanofibers 38 and on graphene oxide; 39 the ATRP of covalently linked polymer chains on the lamellae of a zirconium phosphonate; 40 the ATRP of PMMA on ZnO nanowires; 41 the grafting of PMMA onto silica nanoparticles; 42 the patterning of covalent organic monolayers on Si etc. 43 Moreover, interesting uses of diazonium salts as coupling agents have been recently provided in a reaction in which some azide-funtionalized, hydrolyzed poly(glycidyl methacrylate) was clicked to alkynylated carbon nanotubes, prepared using in situ-generated diazonium salts, and used as initiators for surface-confined photopolymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of vinyl polymer layers has also been reported extensively [29][30][31][32][33][34][35]. It was reported that successful polymer coating of MWCNTs via reversible addition fragmentation chain transfer (RAFT) mediated emulsion polymerization was achievable [29].…”
Section: Carbon Nanostructures Through Interfacial Engineeringmentioning
confidence: 99%
“…The thickness of PAN layer was controlled by adjusting the polymerization time. The covalent attachment of poly(methyl methacrylate) (PMMA) onto the surface of SWCNTs having polymerizable vinyl groups was reported [33]. The SWCNTs functionalized with acrylate group was dispersed in a sodium dodecylbenzene sulfonate (SOBS) emulsifying solution.…”
Section: Carbon Nanostructures Through Interfacial Engineeringmentioning
confidence: 99%
“…It is well known that carboxylic acid (-COOH) groups were first reported in 1998 [21]. Based on the -COOH attachment, many investigations and a variety of functional groups have been carried out to functionalise MWCNTs [20,22]. For instance, Gao et al [22] reported on functionalisation of single-walled carbon nanotubes (SWCNTs) with poly(methyl methacrylate) (PMMA).…”
Section: Introductionmentioning
confidence: 99%